2018
DOI: 10.1111/gbb.12505
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐α‐inhibitor deficiency in the mouse is associated with alterations in anxiety‐like behavior, exploration and social approach

Abstract: In recent years, several genome-wide association studies have identified candidate regions for genetic susceptibility in major mood disorders. Most notable are regions in a locus in chromosome 3p21, encompassing the genes NEK4-ITIH1-ITIH3-ITIH4. Three of these genes represent heavy chains of the composite protein inter-α-inhibitor (IαI). In order to further establish associations of these genes with mood disorders, we evaluated behavioral phenotypes in mice deficient in either Ambp/bikunin, which is necessary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…Similarly, the dysregulation of Ina expression and of Il33 in Table 1 for the CAG100-KIN were similarly reported for ALS [70, 106]. The progressive decrease of Unc13c mRNA levels in Table 1 reflects the specific motor deficits of these mice, in view of its key role in cerebellar parallel fibers for fast reflexes and motor learning [9, 128]; the depletion of Slc6a11 encoding the GABA-transporter-3, and of Gabrb2 encoding the GABA-A-receptor-beta-2, in CAG100-KIN clearly mirrors the dysfunction of GABA-ergic signaling in the spinal dorsal horn and in cerebellar Purkinje cells [63, 86]; the deficiency of Itih3 -encoded protein complexes was documented in Table 1 and occurs similarly after denervation, leading to diminished exploration and anxiety-like behavior in mice [21, 61, 134].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the dysregulation of Ina expression and of Il33 in Table 1 for the CAG100-KIN were similarly reported for ALS [70, 106]. The progressive decrease of Unc13c mRNA levels in Table 1 reflects the specific motor deficits of these mice, in view of its key role in cerebellar parallel fibers for fast reflexes and motor learning [9, 128]; the depletion of Slc6a11 encoding the GABA-transporter-3, and of Gabrb2 encoding the GABA-A-receptor-beta-2, in CAG100-KIN clearly mirrors the dysfunction of GABA-ergic signaling in the spinal dorsal horn and in cerebellar Purkinje cells [63, 86]; the deficiency of Itih3 -encoded protein complexes was documented in Table 1 and occurs similarly after denervation, leading to diminished exploration and anxiety-like behavior in mice [21, 61, 134].…”
Section: Resultsmentioning
confidence: 99%
“…In the brain, we have shown that endogenous IAIPs were reduced 4 hr after ischemia in the fetal sheep, suggesting that changes in endogenous IAIPs could participate in the response to brain ischemia (Spasova et al, ), and findings showing decreased plasma levels of inter‐alpha trypsin inhibitor heavy chain 4 in adult patients with ischemic stroke agree with our previous findings (Kashyap et al, ). In addition, recent work examined behavioral phenotypes in mice deficient in Ambp/bikunin, the light chain of IAIPs (Goulding et al, ). The loss of Ambp/bikunin resulted in augmented anxiety‐like behavior, decreased exploratory activity, increased sex‐dependent acoustic startle responses, and alterations in social approach in mice suggesting a role for the heavy chains, ITIH1/ITIH3, in the development of mood disorders (Goulding et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent work examined behavioral phenotypes in mice deficient in Ambp/bikunin, the light chain of IAIPs (Goulding et al, ). The loss of Ambp/bikunin resulted in augmented anxiety‐like behavior, decreased exploratory activity, increased sex‐dependent acoustic startle responses, and alterations in social approach in mice suggesting a role for the heavy chains, ITIH1/ITIH3, in the development of mood disorders (Goulding et al, ). Polymorphisms of inter‐alpha inhibitor heavy chain 3 are also associated with increased incidences of psychiatric disorders and suicide attempts in patients (Hamshere et al, ; Sasayama et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations